Effect of continuous carbon fiber layup architecture on tensile performance of hybrid FDM composites (Fracture and Structural Integrity, 2026)
Hybrid continuous fiber–reinforced composites produced by fused deposition modeling (FDM) offer a promising solution for lightweight load-bearing structures. However, their mechanical performance is strongly governed by internal reinforcement architecture. This study experimentally investigates the effect of continuous carbon fiber layup orientation on the tensile behavior of hybrid FDM composites based on three short-fiber-reinforced thermoplastic matrices: ABS, PA12, and PET-G. Specimens were fabricated using continuous fiber co-extrusion technology with controlled constant and combined fiber layup schemes. Uniaxial tensile tests with non-contact strain measurement were performed to evaluate Young’s modulus, ultimate tensile strength, and strain-to-failure. Results show that fiber alignment with the load direction is essential for maximizing stiffness and strength, while the polymer matrix primarily controls ductility and failure strain. Combined layups with axially oriented and off-axis layers offer a balance between strength and damage tolerance. Fractographic observations indicate mixed Mode I/Mode II failure governed by structural anisotropy and matrix plasticity. These findings establish the design basics for optimizing hybrid continuous-fiber-reinforced FDM composites and provide a practical framework for the development of additively manufactured structural components.
Keywords: Hybrid 3D-printed composites; short fiber-reinforced polymers; continuous carbon fiber; experimental characterization; microstructure; layup angle